Application of intelligent optical fiber monitoring technology in power optical communication - Yongfeng WANG; Chunjiao LOU; Runbin LIU (Dianxin kexue)
Intelligent optical fiber monitoring technology (eODN)is the advanced network operation and maintenance technology in optical fiber communication. Firstly, the operation and maintenance analysis of the intelligent grid fiber network was carried out. Then, the feasibility of eODN technology in intelligent optical communication was analyzed from the basic principles of eODN, application feasibility, proposal of fault treatment and market application. eODN can realize the intelligent management of power optical fiber network, enhance the reliability of power optical fiber communication and the convenience of network maintenance.